Contação de histórias e o processo de aquisição e desenvolvimento do vocabulário oral da criança na pré-escola - Souza, Luiza Costa de (Brasil, 2022)
The research is qualitative in nature and addresses the storytelling in the process of acquisition and development of the oral vocabulary of children with the objective of investigating how the teacher develops the act of storytelling, with the purpose of acquiring and expanding the vocabulary of 5-year-old children from a public school in Parintins (AM). Therefore, we observe how the storytelling is developed for 5-year-old children, how the teacher performs storytelling to expand the child's vocabulary and finally identify whether the children's retelling of stories was expanded. To achieve the proposed objectives, we conducted a bibliographic study based on the theoretical assumptions to the studies of Nobrega (2017), Teberosky and Sepulvea (2016), Bussato (2012), Abramovich (1989), Dohme (2010), among others and in the documents: BNCC (2018), RCAEI AM (2019). In the construction of the data, participant observation and the realization of workshops for the Counting of Amazonian Legends were used. By analyzing the data obtained in the research we conclude that storytelling in the school environment is a magical, charming, and inspiring moment for children. Therefore, listening, interpreting, and retelling stories are important moments to contribute to the linguistic development of children, in addition to acquiring knowledge of new words. However, it is necessary to enhance this practice in early childhood education with the intention of stimulating linguistic development and expanding the vocabulary of children.